The Intersectionality of Age and Gender on the Bench: Are Younger Female Judges Harsher With Serious Crimes? - Hoffman, Morris B.; Shen, Francis X.; Iyengar, Vijeth; Krueger, Frank (Columbia Journal of Gender and Law, 2020)
We analyzed sentencing data from sixteen years of criminal trials in the State of Colorado, consisting of almost 3,000 individual sentences, and discovered an interaction effect of harm, gender, and age not reported in any of the empirical or experimental literature. Young female judges punished high harm crimes substantially more than their male and older female colleagues. These results, if confirmed, could have significant strategic and tactical implications for practicing lawyers. They may also inform policies surrounding judicial selection, education, training, and retirement.